Leading at a distance : practical lessons for virtual success - Citrin, James M.; DeRosa, Darleen M., 1970- (Wiley, 2021)
"Leading at a Distance is a highly practical guide that leverages the authors' in-depth research and consulting experience--and that of the global leadership advisory firm behind them--to provide a resource for leaders and executives. This book is a hands-on toolkit filled with examples and insights to guide leaders as they navigate virtual work. The book shares tips and best practices to onboard leaders virtually, build trust, shape organizational culture from a distance, enhance top team effectiveness, and conduct high-impact virtual meetings. Working remotely will likely become a more common factor for leaders guiding teams and organizations in the future. In this context, leaders must master virtual work environments to keep geographically dispersed team members aligned, connected, engaged, and performing. Leaders are aware that leading virtual teams and geographically dispersed employees can be very challenging. It is more difficult to hold employees accountable, build trust and strong relationships, as well as coach from a distance. Yet, organizations need to adapt to a virtual way of working as virtual leadership plays an increasingly important role in driving overall organizational effectiveness and performance"--